Review of Data Integrity Checking in Cloud Computing (International Journal of Innovative Research in Computer Science & Technology, 2017)
Cloud computing is the emerging era in many  fields of computing. Here the major role is that storing of user  data and data has to provide to the users whenever they  needed. There are many challenges will takes place to perform  store and providing of information to the user. One of the  challenges in cloud computing is the integrity of the data  stored in cloud. Here we are identifying existing techniques  which are used for data integrity checking in cloud computing.
Keywords: Cloud computing; Integrity